Chromium (Cr) phyto-toxicity effect of Horse gram (Dolichos biflorus L.) - K., Palanisamy; R., Pushpa; M., Lenin (African Science Publications, 2020)
In recent years, Heavy Metals (HMs) pollution has become a serious problem all over the world as these (HMs) continue in the soil for longer period due to their non-biodegradability. The chromium (Cr) is one of the nonessential heavy metal that makes highly toxicity in the plants as well as soil. Cr is one such nutrient required for sugar and fat metabolism in humans, whereas the role of Cr in plant growth and its uptake pathway are not yet fully understood. The pot experiments were carried out of the Horse gram (Dolichos biflorus L.) seeds were raised in pots, the pots containing 2.5 kg of soil with adding different levels of Cr (control, 2, 4, 6, 8 and 10 mg/kg soil). Three replicates were maintained for each level. Morphological parameters like root and shoot length, total leaf area and fresh and dry weights and pigment content and biochemical estimation were recorded in 60th DAS of plants. From the results was concluded that the 2 mg kg-1 level of Cr in the soil was beneficial for the growth of Horse gram. The level of Cr in the soil above 2 mg kg-1 proved to be toxic effects. The results indicated that the 2 mg kg-1 Cr level can be increasing the growth of Horse gram.
Keywords: Chromium, Toxicity, Dolichos biflorus L., Pigments and Biochemical content